The emotion regulation motive of nonsuicidal self-injury mediates the relationship between motor impulsivity and NSSI frequency in adolescents - Ma, Hong; Liu, Xiaoli; Du, Xiangju; Chi, Danni; Zhang, Yuanyuan; Yu, Haihang; Zhou, Dongsheng (Frontiers in Psychiatry, 2025)
BackgroundNonsuicidal self-injury (NSSI) is a common and acute mental health issue among hospitalised adolescents. Although prior research has highlighted the roles of both impulsivity and emotion regulation in self-injurious behaviours, the specific mediating role of the emotion regulation motive in the relationship between motor impulsivity and NSSI frequency remains insufficiently understood.Methods206 adolescents with a history of NSSI were recruited from the Affiliated Kangning Hospital of Ningbo University. Subjects filled out the Ottawa Self-Injury Inventory (OSI) to evaluate the frequency and motives of NSSI behaviours, and the Barratt Impulsivity Scale-11 (BIS-11) to assess impulsivity. We conducted a mediation analysis and employed Causal mediation analysis to test whether emotional regulation function mediates the relationship between motor impulsivity and NSSI frequency.ResultsThe results showed positive correlations between motor impulsivity and frequency of NSSI (r = 0.21, p < 0.01) and emotion regulation motive (r = 0.34, p < 0.01). Causal mediation analysis revealed that motor impulsivity significantly influenced NSSI frequency through emotion regulation, with no direct effect observed (all ADEs, p > 0.05). Specifically, higher motor impulsivity was linked to increased probabilities of engaging in weekly (ACME = 0.0030, p < 0.001) and daily NSSI (ACME = 0.0017, p < 0.001), while emotion regulation mediated approximately 80% of the total effect.ConclusionThe study demonstrates that higher motor impulsivity is associated with a greater likelihood of engaging in weekly and daily NSSI, with emotion regulation motive significantly mediating this relationship. This highlights the need for interventions targeting impulsivity and emotion regulation to address NSSI behaviours in this population effectively.